2017
DOI: 10.1002/2016ja023697
|View full text |Cite
|
Sign up to set email alerts
|

PFISR observation of intense ion upflow fluxes associated with an SED during the 1 June 2013 geomagnetic storm

Abstract: The Earth's ionosphere plays an important role in supplying plasma into the magnetosphere through ion upflow/outflow, particularly during periods of strong solar wind driving. An intense ion upflow flux event during the 1 June 2013 storm has been studied using observations from multiple instruments. When the open‐closed field line boundary (OCB) moved into the Poker Flat incoherent scatter radar (PFISR) field of view, divergent ion fluxes were observed by PFISR with intense upflow fluxes reaching ~1.9 × 1014 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…The high flow velocity may cause strong ion‐frictional heating and enhanced ion temperature (e.g., St.‐Maurice & Hanson, ; Carlson, ; Bjoland et al, ). The enhanced ion temperature can cause rapid recombination of the ionosphere and depletion of the electron density (Rodger et al, ; Zou et al, ).…”
Section: Observationmentioning
confidence: 99%
“…The high flow velocity may cause strong ion‐frictional heating and enhanced ion temperature (e.g., St.‐Maurice & Hanson, ; Carlson, ; Bjoland et al, ). The enhanced ion temperature can cause rapid recombination of the ionosphere and depletion of the electron density (Rodger et al, ; Zou et al, ).…”
Section: Observationmentioning
confidence: 99%
“…In this scenario, the T e enhancement seen in the F region ionosphere is a remote effect, meaning that the low‐energy magnetospheric electrons do not actually penetrate to F region altitudes, so no significant ionization or red‐line auroral excitation is expected to accompany the heating there. However, the change of T e profile would affect the plasma density in the upper F region, for example, due to T e ‐dependent recombination rates of ions (e.g., Bekerat et al, ; David et al, ; Zhu et al, ; Zou et al, ). Also, when T e is sufficiently high the high‐energy tail in the thermal distribution of electrons may exceed the excitation threshold of O ( 1 D ) and cause some moderate 630 nm emissions (Solomon et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Strangeway et al [2005] suggested that ion outflow usually occurs as a two-step process with ion upflow caused by increased ion (so-called Type 1 upflow) and/or increased electron (so-called Type 2 upflow) temperatures in the F region and topside ionosphere as the first step. Recently, enhanced F region and topside ionosphere density within the storm-enhanced density (SED) region [Foster et al, 2005;Zou et al, 2013Zou et al, , 2014 has been suggested to be a third mechanism of contributing large ion upflow fluxes [Semeter et al, 2003;Yuan et al, 2008;Zou et al, 2017]. The first two mechanisms described above arise from plasma temperature increase, while the third one associated with SED is due to increased plasma source population.…”
Section: Introductionmentioning
confidence: 99%
“…Such vertical drift and lifting of the F region ionosphere have been frequently observed within the SED[Zou et al, 2013[Zou et al, , 2014] although the convection flows are associated with different magnetospheric dynamic processes. These vertical drifts and F Geophysical Research Letters 10.1002/2017GL072678 region lifting have been suggested to play an important role in preconditioning intense ion upflow fluxes[Zou et al, 2017].…”
mentioning
confidence: 99%